(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Zeolites are based on aluminosilicate (aluminium (Al), silicon (Si) and oxygen (O)) minerals, containing H2O and metals of the alkaline and alkaline earth groups their empirical formula is M2nO•Al2O3•ySiO2•wH2O, in which n = cation valence, y = 2 to infinity, and w = the water molecules within the framework’s channels. The crystalline structure of zeolites is based on AlO4 and SiO4 tetrahedra that connect to one another through oxygen bonds.The Al and Si tetrahedra are the primary building units (PBU) of the zeolite structure, and the connections between these form the secondary building units (SBU) that then repeat infinitely in a three-dimensional structure.